The Placentian Series: Appearance of the Oldest Skeletalized Faunas in Southeastern Newfoundland - E. Landing; Myrow, P.; Benus, A. P.; Narbonne, G. M. (Journal of Paleontology, 1989)
The lowest Cambrian of Avalon, or Placentian Series, is a relatively thick sequence (1,400 m) in southeastern Newfoundland. A newly proposed body fossil zonation supplements an existing trace fossil zonation of the lower part of the Placentian Series and includes strata to the top of the sub-trilobitic Lower Cambrian. The Sabellidites cambriensis Zone brackets the Precambrian--Cambrian boundary and comprises peritidal and wave-influenced subtidal facies deposited during deepening through the lower part of the Chapel Island Formation. Younger "Ladatheca" cylindrica Zone strata include the deepest facies of the Chapel Island Formation. The base of the overlying Watsonella crosbyi Zone (a post-Nemakit Daldyn and pre-Tommotian equivalent) is significantly diachronous because the diagnostic mollusks were preferentially preserved in pyritiferous offshore muds rather than in coeval nearshore muds. High diversity, upper Watsonella crosbyi Zone faunas (18 species) are limited to peritidal limestones of member 4 and are dominated by calcareous small shelly fossils. A thick interval (ca. 430 m) without body fossils and an important episode of block faulting that led to 750 m of differential erosion preceded deposition of the lower part of the Bonavista Group (=Sunnaginia imbricata Zone, an interval considered to be largely older than the Tommotian). Although much Early Cambrian time may be lost as a result of erosion at Random Formation--Bonavista Group unconformities, many Watsonella crosbyi Zone species reappear in the Sunnaginia imbricata Zone. Shoaling accompanied the immigration event defining the base of the Camenella baltica Zone, and an unconformity following regional offlap marks the top of the Placentian Series. Calcareous, and not phosphatic, composition is most common in earliest Cambrian shelly remains. Little evidence suggests that a global, Precambrian--Cambrian boundary interval "phosphogenic" event either resulted in deposition of local phosphate deposits in the Tethyan region or had a role in the appearance of mineralized skeletons. Twenty metazoans and problematica and an alga are illustrated from the Chapel Island Formation. Bemella? vonbitteri Landing n. sp. and Halkieria stonei Landing n. sp. are described. The monoplacophoran Archaeospira? avalonensis Landing n. sp. has right- and left-handed conchs comparable to those of Archaeospira (=Yangtzespira) from China. Anabarites is the senior generic synonym of Tiksitheca.
Keywords: geology paleontology